(untitled) (Agroindustria, Sociedad y Ambiente, 2021)
In the argumentative course of the essay, a reflective interpretation is exposed from own and other people’s voices about the complex chaotic in uncertain that is the world and the most complex and uncertain that has become a product of the pandemic. It represents a reflection on the concrete reality with looking to configure knowledge. Therefore, its intention is to add to the understanding of a complex, reticular, chaotic and uncertain world, mired in the Covid-19 pandemic. Which leads to greater complexity, greater chaoticity but above all, greater uncertainty. We mainly used the metaphor presented by a contemporary philosopher Byung-Chul Han (2014) "The digital swarm" around which he exposes the social behavior of people in the face of virtuality. It is assumed because the interaction during the time of the quarantine by Covid-19 meant and means our window with the rest of the world. We agree that the pandemic is generating more chaos and uncertainty to the already complex reality that we have to live in this second decade of the new millennium and in a Venezuela plunged in a severe political, economic and energy crisis with its implications in the concrete relationship of living.